RELIABILITY OF SHOULDER ROTATION MOVEMENT MEASURED BY THE SMARTPHONE CLINOMETER APPLICATION - dos Passos, Muana Hiandra Pereira (2022)
Goniometry is widely used to measure range of motion (ROM), but requires skill and training. In this sense, smartphoneapps appear as an alternative. The objective was to assess the reliability and validity of shoulder rotation measurements using asmartphone clinometer app. This study approved by Ethical and Research Committee of the University of Pernambuco. Thirty six(36) healthy and physically active adolescents and young adults participated in the study. In the measurement each volunteerperformed external (ER) and internal (IR) rotation of the shoulder in the supine and side lying positions. The shoulder rotation ROMwas measured by a goniometer and an application. ER and IR were measured in two days by two evaluators. Reliability was determinedusing intraclass correlation coefficient (ICC), standard error of measurement (SEM) and minimum detectable change (MDC). Validitywas assessed using Pearson's correlation coefficients. Both devices had excellent intra- and inter-examiner reliability levels in mostevaluations. However, the goniometer showed moderate inter-examiner reliability in measuring the internal rotation performed in thelying position (ICC 0.61 to 0.67). The app showed inter-examiner reliability ranging from fair to moderate for the same measurements(ICC 0.35 to 0.61). Significant differences were observed between the values recorded by the two instruments for all measurementsperformed (p <0.001). A strong correlation was observed between measurements in the supine and side lying positions with thegoniometer and a smartphone clinometer app (r> 0.85). The application presented excellent reliability levels as well as demonstrateda high correlation with the goniometer. However, the assessment of IR lying down position should be avoided.